The histone deacetylase SIRT6 is a tumor suppressor that controls cancer metabolism - Sebastián, Carlos (2012)
Reprogramming of cellular metabolism is a key event during tumorigenesis. Despite being known for decades (Warburg effect), the molecular mechanisms regulating this switch remained unexplored. Here, we identify SIRT6 as a tumor suppressor that regulates aerobic glycolysis in cancer cells. Importantly, loss of SIRT6 leads to tumor formation without activation of known oncogenes, whereas transformed SIRT6-deficient cells display increased glycolysis and tumor growth, suggesting that SIRT6 plays a role in both establishment and maintenance of cancer. By using a conditional SIRT6 allele, we show that SIRT6 deletion in vivo increases the number, size, and aggressiveness of tumors. SIRT6 also functions as a regulator of ribosome metabolism by corepressing MYC transcriptional activity. Lastly, Sirt6 is selectively downregulated in several human cancers, and expression levels of SIRT6 predict prognosis and tumor-free survival rates, highlighting SIRT6 as a critical modulator of cancer metabolism. Our studies reveal SIRT6 to be a potent tumor suppressor acting to suppress cancer metabolism.